Baseline folic acid status affects the effectiveness of folic acid supplements in cognitively relevant outcomes in older adults: a systematic review - Huang, Ling; Zhao, Jing; Chen, Yongjie; Ma, Fei; Huang, Guowei; Li, Wen (Aging & mental health, 2022)
Folic acid was investigated for decreased concentrations of the same type of cysteine (Hcy), which is considered a risk factor for Alzheimer's disease. However, the conclusions are inconsistent, while supplementing elders with different folic acid states. The PubMed, Science Network and EMBASE databases were searched for randomized controlled trials published over the past decade; The 11/485 study was included on the basis of pre-defined criteria. Cognitive-related results, including cognitive function and brain atrophy, were measured using cognitive scales and magnetic resonance imaging. Significant cognitive benefits were reported in individuals with incomplete folic acid (n s 4); However, individuals with sufficient folic acid (n s 2) do not benefit from supplements, evaluated by the cognitive scale. On the other hand, a significant positive association was established in the participants of plasma Hcy, but the folic acid state was sufficient (n s 2). One study reported that folic acid supplements did not provide any benefit, but folic acid status data were missing. In addition, folic acid supplementation also improves brain atrophy (n s 2). Baseline folic acid status may be a potential factor affecting the results of cognitive function folic acid supplementation in older adults. Older people with insufficient folic acid will benefit from folic acid supplementation.